Wonders of sand and stone : a history of Utah's national parks and monuments - Swanson, Frederick H. (Frederick Harold), 1952- (The University of Utah Press, 2020)
From Delicate Arch to the Zion Narrows, Utah's five national parks and eight national monuments are home to some of America's most amazing scenic treasures, created over long expanses of geologic time. In Wonders of Sand and Stone, Frederick H. Swanson traces the recent human story behind the creation of these places as part of a protected mini-empire of public lands.0 Drawing on extensive historical research, Swanson presents little-known accounts of people who saw in these sculptured landscapes something worth protecting. Readers are introduced to the region's early explorers, scientists, artists, and travelers as well as the local residents and tourism promoters who worked with the National Park Service to build the system of parks and monuments we know today, when Utah's national parks and monuments face multiple challenges from increased human use and from development outside their borders. As scientists continue to uncover the astonishing diversity of life in these desert and mountain landscapes, and archaeologists and Native Americans document their rich cultural resources, the management of these federal lands remains critically important. Swanson provides us with a detailed and timely background to advance and inform discussions about what form that management should take.